Method for optimizing pore channels of magnesium oxide modified biochar
Through biomass degradation, magnesium nitrate microwave foaming and in-situ etching technology, the porous structure is regulated, the problem of insufficient pore structure of biochar is solved, the pollutant removal efficiency is significantly improved, and efficient adsorption performance is achieved.
Patent Information
- Application Number
- CN202411273633.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-12
AI Technical Summary
The pore structure of existing biochar is insufficient, which limits its pollutant removal ability. When magnesium oxide particles are embedded in biochar, it will cause pore size blockage, affecting adsorption performance.
Using biomass degradation, magnesium nitrate microwave foaming and in-situ etching synergistic technology, the porous structure is regulated, and porous magnesium oxide modified biochar with micropores, mesoporous and macropore gradient distribution is distributed, and the formation of graphitized carbon is promoted through alkali solution. , increase the adsorption rate and quantity.
The porous structure is optimized, the adsorption rate and quantity of biochar is improved, the process is simplified, suitable for industrial production, and the pollutant removal efficiency is significantly improved.
Smart Images

Figure CN119215868A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environment and material technology, and relates to a method for optimizing pores of magnesium oxide-modified biochar. Background Art
[0002] In recent years, the water pollution problem caused by the rapid development of industry has become increasingly serious. The national "Comprehensive Wastewater Discharge Standard" (GB8978-1996) and other standards have put forward clear requirements for industrial wastewater discharge. Therefore, achieving efficient removal and recovery of pollutants in wastewater is of great significance to ecological balance and human health. At present, the existing methods for treating water pollutants include biological methods, precipitation methods, adsorption methods, membrane separation and other technologies. Among them, adsorption methods, photocatalysis and other methods have the advantages of easy separation and low cost and are widely used. High adsorption rate and high adsorption capacity adsorbents are key factors in the development of wastewater adsorption materials.
[0003] Biochar is a carbon material prepared from biomass. It has attracted widespread attention due to its wide source and environmental friendliness. Biochar has rich functional groups, excellent physical and chemical stability, and rich pore structure, which makes it have good potential applications in pollutant adsorption. However, the insufficient porosity of the original biochar leads to low removal capacity for many pollutants, which restricts the industrial application of biochar. In order to improve the pore structure and surface functional groups of biochar, researchers have developed solid alkali, acid, metal oxide and oxidant modification technologies. Alkali-activated biochar can etch biochar and expand the pore channels of biochar, but during the pyrolysis process, the alkali reacts violently with biochar to form a large number of macropores and ultra-large pores, which is not conducive to the improvement of adsorption performance. Magnesium oxide-modified biochar has been shown to have good phosphorus adsorption performance. Its common preparation method uses magnesium chloride to impregnate biomass, further pyrolysis to convert magnesium chloride into magnesium oxide and biomass into biochar, and finally obtains magnesium oxide-modified biochar adsorption material. The magnesium oxide formed significantly enhances the adsorption active sites of biochar. However, when magnesium oxide particles are embedded in biochar, the pore size will be blocked, which is not conducive to the transmission of pollutants. In addition, the unreasonable step-by-step pore structure of the modified biochar itself also seriously limits the improvement of the material adsorption capacity. The modification of the pore structure and surface functional groups of biochar alone can no longer meet the requirements of application. Therefore, it is of great significance to develop modified biochar with a micropore-mesopore-macroporous gradient distribution, a porous structure and rich MgO active sites. In order to construct porous modified biochar, Qiu et al. used potassium bicarbonate pyrolysis to activate biochar. The modified biochar obtained had a porous structure and exhibited excellent adsorption performance for para-chlorophenol (DOI: 10.1016 / j.resconrec.2021.105953). In addition, the foaming strategy has been proven to be an effective method for synthesizing porous materials. For example, Han et al. synthesized porous carbon by in situ gas foaming combined with a hard template method. By introducing silica into the polymer, further foaming and carbonization, and removing the silica hard template, porous carbon materials were obtained (DOI: 10.1016 / j.jcis.2023.05.055).
[0004] Therefore, in the absence of literature reports on the in-situ foaming of biomass to prepare porous carbon materials, the present invention cleverly utilizes magnesium nitrate impregnation in-situ microwave-enhanced foaming in conjunction with in-situ etching, and successfully develops a porous magnesium-modified biochar technology, which has not been reported in the literature and is challenging. Summary of the invention
[0005] In order to solve the above problems, the present invention is based on the biomass alkaline degradation, magnesium nitrate high temperature etching, magnesium nitrate foaming strategy, and develops a technology for promoting the optimization of porous magnesium modified biochar pore channels by biomass degradation / in-situ etching / microwave foaming. The micropore volume in biochar is increased by biomass degradation pretreatment; the macropore volume in biochar is increased by magnesium nitrate microwave foaming; the mesopore volume of biochar is increased by magnesium nitrate in-situ etching pyrolysis; the micropore, mesopore, and macropore pore structure regulation in porous magnesium modified biochar can be achieved through the synergistic effect of biomass degradation, in-situ etching, and microwave foaming, and hierarchical pore channel optimization can be achieved. Finally, a porous magnesium oxide modified biochar material with a gradient distribution of micropores, mesopores, and macropores is formed, which can provide scientific channels for pollutants in wastewater to shuttle in the adsorbent, and improve the adsorption rate and adsorption amount of biochar. At the same time, the action of the alkaline solution promotes the formation of graphitized carbon in biochar, which can increase the conductivity of the material and further improve the adsorption rate of magnesium modified biochar. Most importantly, magnesium nitrate has multiple functions in the process of porous material construction: first, magnesium nitrate impregnated in the biomass reacts with the biomass during microwave pretreatment, and produces a foaming effect to increase the proportion of macroporous structure of biomass; second, during pyrolysis, magnesium nitrate will etch the biomass to improve the microporous structure of biochar. Therefore, magnesium nitrate microwave foaming plays an important role in regulating the pore structure of porous biochar materials. This technical process is simple and suitable for industrial production.
[0006] The technical solution of the present invention:
[0007] A method for optimizing the pores of magnesium oxide modified biochar, which increases the volume of micropores in the biochar by biomass degradation pretreatment; increases the volume of macropores in the biochar by magnesium nitrate microwave foaming; increases the volume of mesopores in the biochar by magnesium nitrate in-situ etching and pyrolysis; and achieves micropore, mesopore and macropore structure regulation of porous magnesium modified biochar through the synergistic effect of biomass degradation, in-situ etching and microwave foaming, thereby achieving hierarchical pore optimization; the specific steps are as follows:
[0008] (1) Biomass alkaline degradation: The biomass is washed, dried, and crushed into biomass powder; the biomass powder is added to an alkaline solution, stirred and reacted at 25-90° C. for 1-10 hours, washed with water until neutral, and the alkaline pretreated biomass powder is obtained, and the micropore volume in the biochar is increased;
[0009] (2) Microwave foaming of magnesium nitrate: mixing the biomass powder after alkali pretreatment with an aqueous solution of magnesium nitrate and magnesium acetate to obtain a mixed slurry, and drying the mixed slurry to obtain a mixture; subjecting the mixture to microwave treatment for 1-60 min to obtain a sponge-like biomass, which improves the macroporous structure of the biomass;
[0010] (3) In-situ etching and pyrolysis of magnesium nitrate: The obtained sponge-like biomass is placed in a pyrolysis furnace at 500-900°C and pyrolyzed at high temperature in an inert gas atmosphere for 1-3 hours. The mesoporous volume of the magnesium-modified biochar is increased by etching the biomass with magnesium nitrate to obtain porous magnesium-modified biochar.
[0011] In step (1), the reaction is preferably stirred at 80-90° C. for 6-8 h.
[0012] In step (2), the microwave treatment is performed for 5-20 min, and the microwave power is 600-1000W.
[0013] In step (3), the sponge-like biomass is placed in a 700°C pyrolysis furnace with a heating rate of 2-30°C / min.
[0014] The biomass is one or a mixture of two or more of plant shells, stems, skins, roots, cores, leaves, and animal bones, skins, hairs, and feces.
[0015] The alkaline solution is one or a mixture of two of sodium hydroxide, potassium hydroxide, potassium bicarbonate, sodium bicarbonate, potassium carbonate and sodium carbonate, and the concentration of the alkaline solution is 0.1-2 mol / L.
[0016] The dosage of the magnesium nitrate and magnesium acetate aqueous solutions is controlled so that the mass ratio of magnesium atoms to biomass is 1 to 20:100, preferably 20:100.
[0017] In the magnesium nitrate and magnesium acetate aqueous solution, the mass ratio of magnesium nitrate to magnesium acetate is 1:0.1-10, and the foaming degree and pore structure are adjusted by magnesium nitrate and magnesium acetate in cooperation with microwave assistance.
[0018] Application of porous magnesium oxide modified biochar in pollutant adsorption.
[0019] Beneficial effects of the present invention: The present invention uses biomass degradation / in-situ etching / microwave foaming to synergistically promote the optimization of porous magnesium-modified biochar pores, and realizes the separate regulation of macropores, mesopores, and micropores of porous magnesium-modified biochar. The construction of porous magnesium-modified biochar is achieved through the combined action of alkaline solution-magnesium nitrate-magnesium acetate, wherein magnesium nitrate microwave foaming and pyrolysis etching can respectively improve the macropores and mesoporous structures of the material, which plays a key role in improving the pore structure and adsorption performance of the material. The method has the advantages of simplicity, easy industrialization, high control accuracy, and excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the SEM image of the product in Example 1 of the present invention;
[0021] Figure 2The SEM-mapping diagram of the product of Example 1 of the present invention, wherein (a) is a SEM diagram, (b) is a C element, (c) is a Mg element, (d) is an O element, and (e) is a N element;
[0022] Figure 3 This is the XRD diagram of the product of Example 1 of the present invention;
[0023] Figure 4 This is a SEM image of the product of Example 2 of the present invention;
[0024] Figure 5 This is a SEM image of the product of Example 3 of the present invention;
[0025] Figure 6 This is a SEM image of the product of Example 4 of the present invention;
[0026] Figure 7 This is the SEM image of the product of Comparative Example 1 of the present invention;
[0027] Figure 8 This is the SEM image of the product of Comparative Example 2 of the present invention;
[0028] Fig. 9 This is the SEM image of the product of Comparative Example 3 of the present invention;
[0029] Fig.10 This is the SEM image of the product of Comparative Example 4 of the present invention;
[0030] Fig.11 This is the SEM image of the product of Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0031] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.
[0032] Example 1
[0033] Sodium carbonate was used to pretreat the biomass, magnesium nitrate and magnesium acetate were used to activate the biochar, and microwaves were used. The steps are as follows:
[0034] (1) Biomass alkali degradation: Wash, dry and crush peanut shells into powder for later use; add 2 g peanut shell powder into 30 mL 0.5 mol / L sodium carbonate solution, stir and react at 80° C. for 6 hours, wash with water until neutral, and dry to obtain alkali pretreated biomass powder;
[0035] (2) Microwave foaming: 2.13 g of magnesium nitrate and 1.8 g of magnesium acetate were dissolved in 10 mL of water to obtain a magnesium nitrate / magnesium acetate aqueous solution, with m(Mg):m(biomass)=20:100, peanut shell powder pretreated with mixed alkali was mixed with the magnesium nitrate / magnesium acetate aqueous solution to obtain a mixed slurry, the mixed slurry was dried to obtain a mixture, the mixture was microwaved for 10 minutes, the microwave power was 800 W, and a sponge biomass was obtained;
[0036] (3) In-situ oxidation pyrolysis of magnesium nitrate: The obtained sponge biomass was placed in a 650°C pyrolysis furnace and pyrolyzed at high temperature for 1 hour in an inert gas atmosphere at a heating rate of 5°C / min to obtain porous magnesium oxide modified biochar. Figure 1 , see the face scan Figure 2 , XRD results are shown in Figure 3 .
[0037] The pore structure analysis and SEM results show that the sample has a rich pore structure and presents a porous structure with a macropore-mesopore-micropore gradient distribution. The SEM surface scan results show that the main elements in the sample include carbon, magnesium, oxygen and a small amount of nitrogen. The diffraction peak at 24° in the XRD results is the amorphous peak of biochar, and the diffraction peaks at 36.7°, 42.8°, 62.2°, 74.4° and 78.4° are magnesium oxide (PDF-45-0946), which proves that magnesium oxide is loaded on the surface of biochar. The porous magnesium oxide modified biochar obtained was used for the adsorption of acid fuchsin in wastewater, and the isothermal adsorption results showed that the maximum adsorption amount was as high as 659.27 mg / g. When the initial pollutant concentration was 50 mg / L and the addition amount of porous magnesium oxide modified biochar was 1 g / L, the removal rate of acid fuchsin reached 99.9%.
[0038] Example 2
[0039] Sodium carbonate was used to pretreat biomass, magnesium nitrate and magnesium acetate were used to activate biochar, microwaves were applied, microwave power was increased, and the pore structure of biochar was regulated. The operation steps are as follows:
[0040] (1) Biomass alkali degradation: Wash, dry and crush peanut shells into powder for later use; add 2 g peanut shell powder into 30 mL 0.5 mol / L sodium carbonate solution, stir and react at 80° C. for 6 hours, wash with water until neutral, and dry to obtain alkali pretreated biomass powder;
[0041] (2) Microwave foaming: 2.13 g of magnesium nitrate and 1.8 g of magnesium acetate were dissolved in 10 mL of water to obtain a magnesium nitrate / magnesium acetate aqueous solution, with m(Mg):m(biomass)=20:100, peanut shell powder pretreated with mixed alkali was mixed with the magnesium nitrate aqueous solution to obtain a mixed slurry, the mixed slurry was dried to obtain a mixture, the mixture was microwaved for 10 minutes, the microwave power was 1000 W, and a sponge biomass was obtained;
[0042] (3) In-situ oxidation pyrolysis of magnesium nitrate: The obtained sponge biomass was placed in a 650°C pyrolysis furnace and pyrolyzed at high temperature for 1 hour in an inert gas atmosphere at a heating rate of 5°C / min to obtain porous magnesium oxide modified biochar. Figure 4 .
[0043] The pore structure analysis and SEM results show that the sample has a macropore-mesopore-micropore gradient distribution structure, and its macropore structure is improved compared with Example 1, proving that microwave pretreatment can improve the macropore structure. The porous magnesium oxide modified biochar obtained was used for the adsorption of acid fuchsin in wastewater, and the isothermal adsorption results showed that its maximum adsorption capacity was as high as 613.1 mg / g. When the initial pollutant concentration was 50 mg / L and the amount of porous magnesium oxide modified biochar added was 1 g / L, the acid fuchsin removal rate reached 99.4%.
[0044] Example 3
[0045] Sodium carbonate was used to pretreat biomass, magnesium nitrate and magnesium acetate were used to activate biochar, and compared with Example 1, the amount of magnesium nitrate added was increased, and microwave action was further performed. The operation steps are as follows:
[0046] (1) Biomass alkali degradation: Wash, dry and crush peanut shells into powder for later use; add 2 g peanut shell powder into 30 mL 0.5 mol / L sodium carbonate solution, stir and react at 80° C. for 6 hours, wash with water until neutral, and dry to obtain alkali pretreated biomass powder;
[0047] (2) Microwave foaming: 3.195 g of magnesium nitrate and 0.9 g of magnesium acetate were dissolved in 10 mL of water to obtain a magnesium nitrate / magnesium acetate aqueous solution, with m(Mg):m(biomass)=20:100, peanut shell powder pretreated with mixed alkali was mixed with the magnesium nitrate aqueous solution to obtain a mixed slurry, the mixed slurry was dried to obtain a mixture, the mixture was microwaved for 10 minutes, the microwave power was 800 W, and a sponge biomass was obtained;
[0048] (3) In-situ oxidation pyrolysis of magnesium nitrate: The obtained sponge biomass was placed in a 650°C pyrolysis furnace and pyrolyzed at high temperature for 1 hour in an inert gas atmosphere at a heating rate of 5°C / min to obtain porous magnesium oxide modified biochar. Figure 5 .
[0049] The pore structure analysis and SEM results show that the sample has a rich pore structure and presents a porous structure with a macropore-mesopore-micropore gradient distribution. Compared with Example 1, the micropore content of the product is reduced and the mesopore content is increased. This is because the amount of magnesium nitrate added is increased, which improves the microwave foaming effect and increases the mesopore content. The porous magnesium oxide modified biochar obtained is used for the adsorption of acid fuchsin in wastewater. The isothermal adsorption results show that its maximum adsorption capacity is as high as 632.5 mg / g. When the initial pollutant concentration is 50 mg / L and the amount of porous magnesium oxide modified biochar added is 1 g / L, the acid fuchsin removal rate reaches 99.8%.
[0050] Example 4
[0051] Sodium carbonate was used to pretreat biomass, magnesium nitrate and magnesium acetate were used to activate biochar, and compared with Example 1, the alkali pretreatment time was increased, and microwaves were further applied. The operation steps are as follows:
[0052] (1) Biomass alkali degradation: Wash, dry and crush peanut shells into powder for later use; add 2 g peanut shell powder into 30 mL 0.5 mol / L sodium carbonate solution, stir and react at 80° C. for 10 hours, wash with water until neutral, and dry to obtain alkali pretreated biomass powder;
[0053] (2) Microwave foaming: 2.13 g of magnesium nitrate and 1.8 g of magnesium acetate were dissolved in 10 mL of water to obtain a magnesium nitrate / magnesium acetate aqueous solution, with m(Mg):m(biomass)=20:100, and the peanut shell powder pretreated with mixed alkali was mixed with the magnesium nitrate aqueous solution to obtain a mixed slurry, and the mixed slurry was dried to obtain a mixture, and the mixture was microwaved for 2 minutes at a microwave power of 800 W to obtain a micro-foamed sponge biomass;
[0054] (3) In-situ oxidation pyrolysis of magnesium nitrate: The obtained sponge biomass was placed in a 650°C pyrolysis furnace and pyrolyzed at high temperature for 1 hour in an inert gas atmosphere at a heating rate of 5°C / min to obtain porous magnesium oxide modified biochar. Figure 6 .
[0055] The pore structure analysis and SEM results show that the sample has a rich pore structure and presents a porous structure with a macropore-mesopore-micropore gradient distribution. Compared with Example 1, the alkali pretreatment time of this embodiment is increased, the biomass degradation is increased, and the micropore content of the obtained product is increased compared with Example 1, which proves that alkali pretreatment can control the micropore structure content of the material. The obtained porous magnesium oxide modified biochar was used for acid fuchsin adsorption in wastewater, and the isothermal adsorption results showed that its maximum adsorption capacity was as high as 648.6 mg / g. When the initial pollutant concentration was 50 mg / L and the amount of porous magnesium oxide modified biochar added was 1 g / L, the acid fuchsin removal rate reached 99.8%.
[0056] Comparative Example 1
[0057] The biomass was directly placed in a 650℃ pyrolysis furnace and pyrolyzed at high temperature for 1 hour in an inert gas atmosphere at a heating rate of 5℃ / min to obtain unmodified biochar. Figure 7 .
[0058] Compared with comparative example 2, the SEM results showed that the sample of comparative example 2 had less mesopores and micropores, indicating that the pore structure of the original biochar was underdeveloped. The obtained biochar was used for the adsorption of acid fuchsin in wastewater, and the isothermal adsorption results showed that its maximum adsorption capacity was 3.84 mg / g. When the initial pollutant concentration was 50 mg / L and the amount of porous magnesium oxide modified biochar added was 1 g / L, the acid fuchsin removal rate was 0.15%.
[0059] Comparative Example 2
[0060] Biomass was pretreated by microwave and pyrolyzed to prepare biochar. The steps are as follows:
[0061] (1) Biomass alkali degradation: Wash, dry and crush peanut shells into powder for later use; add 2 g peanut shell powder into 30 mL 0.5 mol / L sodium carbonate solution, stir and react at 80° C. for 6 hours, wash with water until neutral, and dry to obtain alkali pretreated biomass powder;
[0062] (2) The biomass was pretreated with microwaves for 10 minutes at a microwave power of 800 W. No foaming was observed. The biomass was then placed in a 650°C pyrolysis furnace and pyrolyzed at high temperature for 1 hour in an inert gas atmosphere at a heating rate of 5°C / min to obtain biochar. Figure 8 .
[0063] The pore structure analysis and SEM results show that there is no foaming and etching effect of magnesium nitrate. Although the biomass was pretreated with microwaves, the biomass did not foam, and the pore structure of the obtained sample was underdeveloped. However, alkaline degradation pretreatment increased the microporous structure in the biochar. The micropore content of the sample in comparative example 1 was relatively large, indicating that alkaline degradation can increase the micropore content. The obtained biochar was used for the adsorption of acid fuchsin in wastewater, and the isothermal adsorption results showed that its maximum adsorption capacity was 6.22 mg / g. When the initial pollutant concentration was 50 mg / L and the amount of porous magnesium oxide modified biochar added was 1 g / L, the acid fuchsin removal rate was 3.5%.
[0064] Comparative Example 3
[0065] The biochar was activated by single magnesium acetate and microwave treatment. The operation steps are as follows:
[0066] (1) Biomass alkali degradation: Wash, dry and crush peanut shells into powder for later use; add 2 g peanut shell powder into 30 mL 0.5 mol / L sodium carbonate solution, stir and react at 80° C. for 6 hours, wash with water until neutral, and dry to obtain alkali pretreated biomass powder;
[0067] (2) Microwave foaming: 3.6 g of magnesium acetate was dissolved in 10 mL of water to obtain a magnesium acetate aqueous solution, m(Mg):m(biomass)=20:100, peanut shell powder pretreated with mixed alkali was mixed with the magnesium acetate aqueous solution to obtain a mixed slurry, the mixed slurry was dried to obtain a mixture, the mixture was microwaved for 10 minutes, the microwave power was 800 W, and the biomass particles were obtained without foaming;
[0068] (3) Pyrolysis: The biomass was placed in a 650°C pyrolysis furnace and pyrolyzed at high temperature for 1 hour in an inert gas atmosphere at a heating rate of 5°C / min to obtain magnesium oxide-modified biochar. Fig. 9 .
[0069] The pore structure analysis and SEM results show that although magnesium acetate was added for activation, there was no foaming and etching effect of magnesium nitrate. Although the biomass was pretreated with microwaves, the biomass did not foam, and the pore structure of the obtained sample was underdeveloped. However, alkaline degradation pretreatment increased the microporous structure in the biochar. The obtained biochar was used for the adsorption of acid fuchsin in wastewater, and the isothermal adsorption results showed that its maximum adsorption capacity was 214.6 mg / g. When the initial pollutant concentration was 50 mg / L and the addition amount of magnesium oxide-modified biochar was 1 g / L, the acid fuchsin removal rate was 83.6%. The surface modification of magnesium oxide on the surface can achieve partial adsorption of the dye, but due to the underdeveloped pore structure, the dye removal rate and adsorption amount are insufficient.
[0070] Comparative Example 4
[0071] The biochar was activated with magnesium nitrate alone without microwave treatment. The operation steps are as follows:
[0072] (1) Biomass alkali degradation: Wash, dry and crush peanut shells into powder for later use; add 2 g peanut shell powder into 30 mL 0.5 mol / L sodium carbonate solution, stir and react at 80° C. for 6 hours, wash with water until neutral, and dry to obtain alkali pretreated biomass powder;
[0073] (2) Drying: 4.27 g of magnesium nitrate was dissolved in 10 mL of water to obtain a magnesium nitrate aqueous solution, m(Mg):m(biomass)=20:100, peanut shell powder pretreated with mixed alkali was mixed with the magnesium nitrate aqueous solution to obtain a mixed slurry, the mixed slurry was dried to obtain a mixture, and the biomass was further dried at 80° C. to obtain biomass, and the obtained biomass particles were free of foaming;
[0074] (3) In-situ oxidation pyrolysis of magnesium nitrate: The biomass was placed in a 650°C pyrolysis furnace and pyrolyzed at high temperature for 1 hour in an inert gas atmosphere at a heating rate of 5°C / min to obtain magnesium oxide-modified biochar. The SEM results are shown in Fig.10 .
[0075] The pore structure analysis and SEM results show that the sample has a porous structure. The etching effect of magnesium nitrate improves the mesoporous structure of the biochar, but the macropore content of the material is relatively low due to the lack of microwave pretreatment. The porous magnesium oxide modified biochar obtained was used for the adsorption of acid fuchsin in wastewater. The isothermal adsorption results showed that its maximum adsorption capacity was as high as 384.38 mg / g. When the initial pollutant concentration was 50 mg / L and the amount of porous magnesium oxide modified biochar added was 1 g / L, the acid fuchsin removal rate reached 93.4%.
[0076] Comparative Example 5
[0077] Magnesium nitrate and magnesium acetate were used to activate biochar without microwave treatment. The operation steps are as follows:
[0078] (1) Biomass alkali degradation: Wash, dry and crush peanut shells into powder for later use; add 2 g peanut shell powder into 30 mL 0.5 mol / L sodium carbonate solution, stir and react at 80° C. for 6 hours, wash with water until neutral, and dry to obtain alkali pretreated biomass powder;
[0079] (2) Drying: 2.13 g of magnesium nitrate and 1.8 g of magnesium acetate were dissolved in 10 mL of water to obtain a magnesium nitrate aqueous solution, with m(Mg):m(biomass) = 20:100, and the peanut shell powder pretreated with mixed alkali was mixed with the magnesium nitrate aqueous solution to obtain a mixed slurry, which was further dried at 80° C. to obtain a mixture, and biomass particles without foaming were obtained;
[0080] (3) In-situ oxidation pyrolysis of magnesium nitrate: The biomass was placed in a 700°C pyrolysis furnace and pyrolyzed at high temperature for 1 hour in an inert gas atmosphere at a heating rate of 5°C / min to obtain porous magnesium oxide modified biochar. The SEM results are shown in Fig.11 .
[0081] The pore structure analysis and SEM results show that the sample has a porous structure. The etching effect of magnesium nitrate improves the mesoporous structure of biochar. The addition of magnesium acetate regulates the etching degree of magnesium nitrate, inhibits its oxidation performance, and reduces the mesoporous content compared to Comparative Example 4. However, due to the lack of microwave pretreatment, the macroporous content of the material is relatively low. The porous magnesium oxide modified biochar obtained was used for the adsorption of acid fuchsin in wastewater, and the isothermal adsorption results showed that its maximum adsorption capacity was as high as 328.53 mg / g. When the initial pollutant concentration was 50 mg / L and the amount of porous magnesium oxide modified biochar added was 1 g / L, the acid fuchsin removal rate reached 96.6%.
[0082] The above samples were tested for acid fuchsin dye adsorption performance. The test method was to add 0.05g of adsorbent to the acid fuchsin solution, and adsorb it under constant temperature oscillation at 25°C and 180rpm. The acid fuchsin removal rate was determined, and the adsorption experiment was conducted using the isothermal adsorption method. The maximum adsorption amount of the material was calculated using the Langmuir model. The pore volume of the sample was determined using a specific surface area analyzer, and the proportion of micropores (<2nm), mesopores (2-50nm) and macropores (>50nm) in the total pore volume was calculated based on the pore distribution data.
[0083] Table 1 Pore structure and acid fuchsin removal rate
[0084]
Claims
1. A method for optimizing the pores of magnesium oxide-modified biochar, characterized in that: Here are the steps: (1) Biomass alkaline degradation: The biomass is washed, dried, and crushed into biomass powder; the biomass powder is added to an alkaline solution, stirred and reacted at 25-90° C. for 1-10 hours, washed with water until neutral, and the alkaline pretreated biomass powder is obtained, and the micropore volume in the biochar is increased; (2) Microwave foaming of magnesium nitrate: mixing the biomass powder after alkali pretreatment with an aqueous solution of magnesium nitrate and magnesium acetate to obtain a mixed slurry, and drying the mixed slurry to obtain a mixture; subjecting the mixture to microwave treatment for 1-60 min to obtain a sponge-like biomass, which improves the macroporous structure of the biomass; (3) In-situ etching and pyrolysis of magnesium nitrate: The obtained sponge-like biomass is placed in a pyrolysis furnace at 500-900°C and pyrolyzed at high temperature in an inert gas atmosphere for 1-3 hours. The mesoporous volume of the magnesium-modified biochar is increased by etching the biomass with magnesium nitrate to obtain porous magnesium-modified biochar.
2. The method according to claim 1, characterized in that In step (1), the reaction is preferably stirred at 80-90° C. for 6-8 h.
3. The method according to claim 1, characterized in that In step (2), the microwave treatment is performed for 5-20 min, and the microwave power is 600-1000W.
4. The method according to claim 1, characterized in that: In step (3), the sponge-like biomass is placed in a 700°C pyrolysis furnace with a heating rate of 2-30°C / min.
5. The method according to claim 1, characterized in that The biomass is one or a mixture of two or more of plant shells, stems, skins, roots, cores, leaves, and animal bones, skins, hairs, and feces.
6. The method according to claim 1, characterized in that The alkaline solution is one or a mixture of two of sodium hydroxide, potassium hydroxide, potassium bicarbonate, sodium bicarbonate, potassium carbonate and sodium carbonate, and the concentration of the alkaline solution is 0.1-2 mol / L.
7. The method according to claim 1, characterized in that The dosage of the magnesium nitrate and magnesium acetate aqueous solutions is controlled so that the mass ratio of magnesium atoms to biomass is 1 to 20:
100.
8. The method according to claim 1, characterized in that In the magnesium nitrate and magnesium acetate aqueous solution, the mass ratio of magnesium nitrate to magnesium acetate is 1:0.1-10.
9. Use of the porous magnesium-modified biochar obtained by the method according to any one of claims 1 to 8 in pollutant adsorption.
Citation Information
Patent Citations
Preparation method of magnesium-enriched biochar for synchronously and efficiently recycling nitrogen and phosphorus nutrients in farm waste liquid and application of magnesium-enriched biochar
CN110270310A
Method for synthesizing high-porosity magnesium oxide modified biomass charcoal from light burning powder
CN113231028A
Modified leaf biochar as well as preparation method and application thereof
CN114797767A
Magnesium oxide modified charcoal / attapulgite composite material as well as preparation method and application thereof
CN117920142A
Biochar-alginate bead for processing heavy metal contaminated water using biochar powder and manufacturing method thereof
KR101409721B1
Cited By
Application of charcoal / metal oxide composite material in antibiotic elimination
CN120423640A